Implementasi Teknologi Digital dalam Pendidikan Agama di Sekolah Dasar Juara : Upaya Meningkatkan Efektivitas Pembelajaran - Maryam Sulaeman; Ahmad Raya Maulana; Faris Hissi; Putri Alifah; Zahra Eka Sawitri; Yuli Marlina (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
This study aims to identify and analyze the application of digital technology in learning and school activities at SD Juara, East Jakarta, with a focus on the integration of religious values ??and student character development. This study also explores how technology supports the learning process, extracurricular activities, and school management. The research method used is direct observation and documentation of learning activities, the use of technological devices, and the implementation of extracurricular programs. Data collected include the use of hardware (such as computers, projectors, tablets) and software (LMS, digital learning applications), as well as the practice of integrating religious values ??through programs such as reading wirid, Muhadhoroh, and Jumat Berkah. The results of the study show that technology is effectively integrated into learning and school activities. The use of technological devices helps students understand the material interactively, improves digital skills, and strengthens religious values ??through spiritual-based programs. Teachers and school management utilize technology for teaching and administrative efficiency. In addition, technology-based extracurricular activities, such as coding and podcasting, support student creativity. Challenges identified include the need for teacher training and infrastructure maintenance. Overall, SD Juara, East Jakarta has succeeded in creating a holistic education model that combines modern technology with religious-based education to form a generation with character and technological skills